The Moderating Role of Islamic Lifestyle in the Relationship Between Cognitive Emotion Regulation and Mobile Dependency in Kermanshah's Aadolescent Girls in 2017 - Zeynab RostamiNasab DolatAbad; Fatemeh Ehsanpour; Mohyedin Mohammadkhani; Ali Shariatmadar Tehrani; Neda Bagheri Mahyari (Shahid Beheshti University of Medical Sciences, 2019)
For downloading the full-text of this article please click here. Background and Objective: The use of mobile phones has recently become an indispensable part of life. Although mobile phones have several advantages, their excessive use can make individuals prone to dependence. The aim of this study was to investigate the moderating role of Islamic lifestyle in the relationship between cognitive emotion regulation and mobile dependency in adolescent girls. Method: The present study is a descriptive cross-sectional study of correlation type. The statistical population of the study consisted of all secondary school girl students in Kermanshah. Four hundred individuals were selected through multistage cluster random sampling. To collect data, subjects responded to Islamic lifestyle standards (LLST), cognitive/emotional regulation questionnaire (CERQ) and mobile phone harm survey (COS). In order to analyze the data, structural equation modeling was used. All ethical issues were observed in this study and the researchers declared no conflict of interests. Results: The results showed that cognitive/emotional adjustment and Islamic lifestyle are considered good predictors of mobile dependency. Also, based on the findings of structural equation modeling, there are significant and positive causal relationships between cognitive/emotional adjustment, Islamic lifestyle and mobile dependency. Moreover, the mediating role of Islamic lifestyle in the relationship between cognitive/emotional adjustment and mobile dependency was confirmed. Conclusion: The findings suggest that the use of Islamic lifestyle as a coping strategy in people with negative cognitive/emotional adjustment will prevent cell phone addiction. For downloading the full-text of this article please click here.